Understanding the Dynamics of the Developing Adolescent Brain Through Team Science - Zanolie, Kiki; Ma, Ili; Bos, Marieke G. N.; Schreuders, Elisabeth; Vandenbroucke, Annelinde R. E.; van Hoorn, Jorien; van Duijvenvoorde, Anna C. K.; Wierenga, Lara; Crone, Eveline A.; Güroğlu, Berna (Frontiers in Integrative Neuroscience, 2022)
One of the major goals for research on adolescent development is to identify the optimal conditions for adolescents to grow up in a complex social world and to understand individual differences in these trajectories. Based on influential theoretical and empirical work in this field, achieving this goal requires a detailed understanding of the social context in which neural and behavioral development takes place, along with longitudinal measurements at multiple levels (e.g., genetic, hormonal, neural, behavioral). In this perspectives article, we highlight the promising role of team science in achieving this goal. To illustrate our point, we describe meso (peer relations) and micro (social learning) approaches to understand social development in adolescence as crucial aspects of adolescent mental health. Finally, we provide an overview of how our team has extended our collaborations beyond scientific partners to multiple societal partners for the purpose of informing and including policymakers, education and health professionals, as well as adolescents themselves when conducting and communicating research.